Analisis Prinsip Keadilan Dalam Pembiayaan Mudharabah Di BMT Surya Madani Boyolali Jawa Tengah - Candra, Diki; Wulandari, Fitri (Iqtisad: Journal of Islamic Economic and Civilization, 2025)
This study aims to analyze the implementation of the principle of fairness in mudharabah financing at BMT Surya Madani, Boyolali, Central Java, which is one of the main pillars of the Islamic economy. The importance of this study lies in the need for transparent and fair management of Islamic financing to increase public trust in Islamic microfinance institutions. The method applied is a qualitative approach with data collection techniques that include in-depth interviews, document analysis, and direct observation. The results of the study indicate that although the principle of fairness has been applied through the proportional distribution of profits and risks, there are challenges in its implementation, such as the lack of customer understanding of the concept of mudharabah. The novelty of this study lies in the determination of specific factors that influence the application of justice locally, as well as policy implications that prioritize strengthening sharia-based education and supervision to improve the efficiency and sustainability of mudharabah financing.